ANALYSIS OF URBAN TRAFFIC FLOW PERFORMANCE ON RAJAWALI STREET SURABAYA OLD TOWN - Alifian, Muhammad Hilmi; Tjendani, Hanie Teki (Departement of Civil Engineering, Universitas Winaya Mukti, 2025)
The Surabaya Old Town Tourism Area, particularly along Rajawali street, has experienced increased traffic activity due to the high number of tourist visits, especially on weekends. This situation has led to roadside frictions that impact road performance. This study aims to analyze the roadside frictions and traffic volume along the road segment. A quantitative approach was applied, based on the Indonesian Highway Capacity Manual (MKJI) 1997. Primary data were collected through field surveys conducted over seven consecutive days during peak hours (4:00 PM–8:00 PM) and analyzed to identify traffic characteristics at the study location. The results of the study showed that side obstacles were in the moderate to high category, with the highest traffic volume of 2,881 smp/hour on Saturday.